Fumeless Cities and Death Rays: An Archaeology of Fantastic Energy Sources in Polish Science Fiction of the Interwar Period - Stachowicz, Jerzy (Stan Rzeczy, 2025)
The paper reviews the most important, in the author’s opinion, visions of alternative and futuristic ways of producing energy in Polish science-fiction literature before 1939: from electricity generated by hydroelectric turbines through solar rays to radioactivity. The author wonders whether such ideas of energy transformations are still relevant and whether various kinds of pop-cultural visions of the future from the twenty-first century are characterised by unconscious reproduction of modernisation and modernist narratives from a hundred years ago. The theoretical framework of this paper draws upon Richard Barbrook’s concepts of imaginary futures and Charles Taylor’s social imaginaries, as well as Siegfried Zielinski’s concept of media archaeology.